Physical activity and vascular disease in a prospective cohort study of older men: The Health In Men Study (HIMS). Issue 1 (December 2015) - Lacey, Ben; Golledge, Jonathan; Yeap, Bu; Lewington, Sarah; Norman, Paul; Flicker, Leon; Almeida, Osvaldo; Hankey, Graeme
Abstract Background The dose–response relationship between volume of physical activity and incidence of major vascular events at older age is unclear. We aimed to investigate this association in a cohort of older men. Methods For this prospective cohort study, 7564 men aged 65–83 years and without prior vascular disease were recruited in 1996–99 from the general population in Perth, Western Australia. Men were followed up using the Western Australian Data Linkage System to identify deaths and hospitalisations. During mean follow-up of 11 (SD 4) years, there were 1557 first major vascular events: 833 ischaemic heart disease events, 551 stroke events and 173 other vascular events. Cox regression was used to calculate hazard ratios (adjusted for age, education and smoking) for incidence of major vascular events by volume of baseline recreational physical activity (measured in metabolic equivalent [MET] hours per week). Results Hazard ratios among men who performed 0, 1–14, 15–24, 25–39, ≥40 MET-hours per week of recreational physical activity were 1.00 (95 % CI 0.91–1.10; referent), 0.88 (0.79–1.00), 0.81 (0.72–0.91), 0.81 (0.72–0.91) and 0.80 (0.71–0.89), respectively (Ptrend =0.006). The association was slightly attenuated with further adjustment for BMI. There was evidence of stronger associations at older ages and greater intensity of activity, but no evidence of effect modification by smoking, alcohol intake or BMI. There was also no evidence that the association varied by type of vascular event. Conclusions Among men aged over 65 years, there was a curvilinear association between recreational physical activity and incidence of major vascular events, with an inverse association up to about 20 MET-hours per week (equivalent to 1 h of non-vigorous, or half an hour of vigorous, physical activity per day) and no evidence of further reductions in risk thereafter.